Comparison Of The C4.5 And Naïve Bayes Algorithm For Recommendations For Aid Recipients For The Smart Indonesian Program - Rahmat Hidayat; Miftahul Huda; Nanang Pradita (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Indonesian Smart Program (Program Indonesia Pintar “PIP”) is a government backing program aimed at scholars who come from poor or vulnerable families to finance education. Scholars entering PIP correspond of two orders, scholars who have a Indonesian Smart Card (Kartu Indonesia Pintar) Indonesian Health Card (Kartu Indonesia Sehat) and scholars who are recommended by the academy to get an education. The conventional way carried out by seminaries in furnishing education recommendations takes a long time and is prone to mismatch recommendations so that it can affect in the distribution of PIP backing that isn't on target. From these problems the authors are interested in conducting exploration by exercising data mining ways. This exploration compares the C4.5 algorithm and the Naive Bayes algorithm. Testing was carried out on 139 SDN 03 Karanganyar pupil data. The results of the test set up that the C4.5 algorithm is better than the naive bayes algorithm. So that the Rule generated by the C4.5 algorithm can be used to make a decision-making system at SDN 03 Karanganyar